XIX зууны үеийн монголчуудын гоо зүйн сэтгэлгээний асуудал: Issues on aesthetic thinking of the Mongolian philosophers in the XIX century - Б., Дэлгэрмаа (Mongolian Studies, 2023)
In this article, the author tries to investigate the aesthetic thinking of the Mongolian philosophers in the XIX century. Beauty is studied as the main part of aesthetics-it is considered to be a combination of inner beauty and outer beauty by Mongolian philosophers. Criticized and civilized tendencies appeared in art of the XIX century.